2019
DOI: 10.1002/ajb2.1323
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic conductance, resistance, and resilience: how leaves of a tropical epiphyte respond to drought

Abstract: Premise Because of its broad range in the neotropical rainforest and within tree canopies, the tank bromeliad Guzmania monostachia was investigated as a model of how varying leaf hydraulic conductance (Kleaf) could help plants resist and recover from episodic drought. The two pathways of Kleaf, inside and outside the xylem, were also examined to determine the sites and causes of major hydraulic resistances within the leaf. Methods We measured leaf hydraulic conductance for plants in the field and laboratory un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…The ecological stresses of the epiphytic habitat have likely selected for traits to accommodate water deficit in all residing plant lineages. For example, epiphytic angiosperms exhibit high adaptive capacity to maintain a positive leaf water balance, including both drought tolerance and avoidance mechanisms, tank water storage (in bromeliads), foliar water uptake and higher leaf capacitance (Benzing & Burt, 1970; Gotsch et al, 2015; North et al, 2019; Zotz, 2016). Greater morphological diversity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The ecological stresses of the epiphytic habitat have likely selected for traits to accommodate water deficit in all residing plant lineages. For example, epiphytic angiosperms exhibit high adaptive capacity to maintain a positive leaf water balance, including both drought tolerance and avoidance mechanisms, tank water storage (in bromeliads), foliar water uptake and higher leaf capacitance (Benzing & Burt, 1970; Gotsch et al, 2015; North et al, 2019; Zotz, 2016). Greater morphological diversity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we stress the need for CAM syndromes to be assessed in their entirety: the regulation of CO 2 supply and evaporative demand as expressed by stomata, the mesophyll metabolic processes and the limitations imposed by low mesophyll conductance in dense tissues with low airspaces. These aspects need to be integrated with how water supply is monitored, metered and recharged when intermittent external sources are available to roots or leaf rosettes (Griffiths, ; Males and Griffiths, ; North et al , ). We hope these challenges will continue to attract future generations of researchers who can identify the peculiar attraction required to ‘work the night shift’ with CAM (Black and Osmond, ) and determine the extent that CAM systems could contribute to more sustainable biomass production in a changing world.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it is also becoming evident that we need to partition the overall hydraulic conductance into xylem (Kx) and mesophyll (Kox) components to sites of evaporation (Scoffoni et al, 2018;Males and Griffiths, 2018). Whilst even in C3 leaves it is increasingly found that Kox represents a major limitation in the transport of water (Scoffoni et al, 2018), this is also likely to be true for succulent CAM leaves given the relatively high whole-leaf water potentials (about À1 MPa) retained even during an extensive drought (Borland et al, 2009;Griffiths, 2013;Males and Griffiths, 2018;North et al, 2019). Finally, the likely susceptibility to xylem cavitation (i.e.…”
Section: The Compromise Between Carbon Uptake and Water Loss: Hydraulmentioning
confidence: 99%
See 1 more Smart Citation
“…A somewhat paradoxical corollary between pH and light exposure is that, presumably, transpirational demands would be greatest when water uptake from the tank could be limited by possible inhibition of aquaporins due to low pH (Kamaluddin and Zwiazek, 2004 ; Zhang and Zwiazek, 2016 ). In the case of the species central to this study, Guzmania monostachia (L.) Rusby ex Mez (Bromeliaceae), stomatal opening is quite sensitive to light, and stomatal conductance decreases markedly with decreasing light (Maxwell et al, 1994 ; North et al, 2013 , 2016 , 2019 ); thus, low tank pH would seem to be disadvantageous when transpiration is high. On the other hand, one possible benefit of aquaporin inhibition by low pH could be to prolong the availability of water and nutrients by limiting water uptake from the tank at times of peak demand.…”
mentioning
confidence: 99%